POLYMORPHISMS OF MATRIX METALLOPROTEASES 2 AND 9 GENES IN ASCENDING AORTA ANEURISM PATIENTS - N. D. Gavrilyuk; O. B. Irtyuga; T. A. Druzhkova; V. E. Uspensky; A. B. Malashicheva; A. A. Kostareva; O. M. Moiseeva (Российский кардиологический журнал, 2015)
Aim. To study the role of mononucleotide polymorphisms of the matrix metalloproteases genes MMP2 and MMP9 in the development of ascending aorta aneurism (AOA).Material and methods. Totally 287 patients included with AOA and 227 persons of control group. All patients underwent echocardiography and assessment of mononucleotide gene polymorphisms of MMP2 (rs2285053) and MMP9 (rs11697325, rs2274755, rs17577) real-time, by PCR.Results. The association of MMP9 (rs11697325) is confirmed for the formation of AOA. AA genotype was significantly more prevalent among AOA patients (c2 =7,2; p=0,01). AA genotype carriers had higher ascending aorta diameter comparing to other persons with different variants (p=0,02). The relation is shown of the polymorphism ММР2 (rs2285053) and AOA development. Persons with CC genotype were more prevalent in the group of the aorta pathology patients (c2 =7,0; р=0,03).Conclusion. Genetic variants ММР9 and ММР2 can be additional risk factors of ascending aorta aneurism development. Therefore the assessment of different polymorphisms of matrix metalloproteases genes is useful for the risk stratification of the patients with ascending aorta dilation.